(untitled) (Texas Journal of Medical Science, 2024)
The etiology, pathogenesis, and epidemiology of metabolic syndrome in childhood and adolescence are discussed. Criteria for diagnosing the main components of the metabolic syndrome are proposed: obesity, arterial hypertension, hyperglycemia, hypertriglyceridemia, hypoalphacholesterolemia. The problem of metabolic syndrome is considered from the standpoint of vascular risk, issues of diagnosing damage to the cardiovascular system and the development of endothelial dysfunction, arterial hypertension, and dyslipoproteinemia are discussed. Approaches to prevention and treatment are outlined